2014
DOI: 10.1517/17460441.2014.915309
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in technologies for developing drugs againstChlamydia pneumoniae

Abstract: Based on current knowledge, it is important for researchers to continue to focus on phenotypic assays on persistent infections. There should also be a careful evaluation of the physicochemical properties of the lead candidates and attempts toward more narrow-spectrum antibacterial agents. All these elements are important for successful lead generation. The recent advances in understanding C. pneumoniae biology and breakthroughs in genetic transformation are likely to improve the potential for identifying and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…Owing to its propensity for persistence, C. pneumoniae is a challenging target for antibacterial therapy. The bacterium can be eradicated from permissive cell lines such as the airway epithelium by macrolide and tetracycline antibiotics [14] but its complete eradication remains challenging. New strategies for combatting the persistent chlamydial populations are thus needed.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its propensity for persistence, C. pneumoniae is a challenging target for antibacterial therapy. The bacterium can be eradicated from permissive cell lines such as the airway epithelium by macrolide and tetracycline antibiotics [14] but its complete eradication remains challenging. New strategies for combatting the persistent chlamydial populations are thus needed.…”
Section: Introductionmentioning
confidence: 99%
“…C . pneumoniae is resistant to sulfa drugs and trimethoprim, and treatment with penicillins can trigger the formation of a persistent state [ 5 ]. Treatment of C .…”
Section: Introductionmentioning
confidence: 99%
“…Up to 30% of patients with C . pneumoniae -caused community acquired pneumonia harbor the bacterium in a cultivable form even after the treatment and symptoms have ceased [ 5 , 6 ]. Upon treatment failures and non-treated infections, the bacterium may convert to a chronic form characterized by morphological, transcriptional and metabolic changes different from the acute infectious phase.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous review article, we have discussed the nonconventional antichlamydial agents identified within past ten years and highlighted the need for more narrow-spectrum or even chlamydia-specific antibacterial agents [7]. In the current contribution, we focus on describing the different approaches for antichlamydial drug discovery, with illustrative examples of successful use of each of them.…”
Section: Introductionmentioning
confidence: 99%